Exacerbation of Psoriasis Following COVID-19 Vaccination: Report From a Single Center - Huang, Yi-Wei; Tsai, Tsen-Fang (Frontiers in Medicine, 2021)
The temporal association had been reported between vaccination and exacerbation of psoriasis, and episodes of psoriasis flare-up have recently been attributed to COVID-19 vaccines. We recruited 32 unimmunized controls and 51 vaccinated psoriasis patients, 49 of whom were under biological therapy, with regular clinic visits receiving a total of 63 shots vaccines, including 30 doses of Moderna mRNA-1273 and 33 doses of AstraZeneca-Oxford AZD1222. Fifteen episodes of exacerbation attacked within 9.3 ± 4.3 days, which is higher than two episodes in the control group (p=0.047). The mean postvaccination severity of the worsening episodes increased from PASI 3.1 to 8.0 (p < 0.001). Three patients showed morphologic change from chronic plaque-type to guttate psoriasis. Deterioration of psoriasis following COVID-19 vaccination was not associated with age, sex, disease duration, psoriatic arthritis, family history of psoriasis, history of erythroderma, current biologics use, comorbidities, vaccine types, human leukocyte antigen (HLA)-C genotypes, baseline PASI nor prevaccination PASI. For those who received two doses of vaccination, all but one patient aggravated after the first shot but not the second. The mechanism of psoriasis exacerbation in immunized individuals is unclear, but Th17 cells induced by COVID-19 vaccines may play a role. In the pandemic era, psoriasis patients and physicians should acknowledge the possibility of fluctuation of disease activity when vaccinated against COVID-19. Nevertheless, compared to a treatable dermatologic disease with rapid resolution of exacerbation, psoriasis patients who do not have contraindications to vaccination should benefit from COVID-19 vaccines in the prevention of severe COVID-19 infection and fatality.